Perlindungan Hak Konstitusional dari Privatisasi Kelautan: Pendekatan Sistemik Pemulangan Hak yang Dipengaruhi oleh Pagar Kelautan - Alkhair, Rayyan; Muhtada, Dani (Hang Tuah Law Journal, 2025)
The construction of Pantai Indah Kapuk 2 (PIK 2), a waterfront city mega-project in Tangerang, Indonesia, has raised legal, social, and environmental concerns. While designated as a National Strategic Project (PSN) due to its economic benefits, such as job creation and green tourism development, the project has caused significant adverse impacts. Specifically, a 30-kilometer sea fence obstructed access for approximately 4,000 fishermen, resulting in an estimated economic loss of IDR 16 billion since September 2024. This study examines the constitutionality of sea privatization through land certificates (SHM and SHGB) issuance and evaluates government responses to this issue. Using a normative juridical approach, the research analyzes legal frameworks governing coastal resource management, including UNCLOS 1982 and Indonesian laws such as Law No. 27/2007 and Law No. 26/2007. The findings reveal that government actions—sealing the area, dismantling the sea fence with military assistance, and revoking SHM/SHGB—align with regulations but lack systemic coordination. Key issues remain unresolved: criminal prosecution of perpetrators, economic restitution for affected fishermen, and environmental rehabilitation. This article proposes a systemic approach to restoring fishermen's rights through criminal enforcement against illegal actors, financial compensation for economic losses, ecosystem restoration, and strengthening public participation in spatial planning. Drawing lessons Australia's Community Participation Plans (CPP), the study emphasizes inclusive development that balances economic growth with social justice and environmental sustainability.